KEPRIBADIAN PADA TOKOH DALAM NOVEL RINDU KARYA TERE LIYE DAN RELEVANSINYA - Maya Oktavia; Edi Suyanto (FKIP Universitas Lampung, 2016)
The purpose of this research was to describe the personality of figures experienced by the figures in the Rindu novel and its relevance in teaching literature in high school which includes das ice (id), das ich (ego), and das ueber ich (superego) in terms of three aspects language, psychology, and cultural backgrounds. Method in this research was descriptive qualitative. Data sources this research novel was Rindu work Tere Liye. Technique data analysis in this research was reduction data, presentation of data, and the withdrawal of conclusion. The result analysis showed that personality conflict category id is 4 , ego is 72, and the superego is 25 so a whole data of personality conflict obtained is 101 data. So it can be concluded that personality that there are on type of personality ego with the data as many 72. Next, the results of that the analysis above novel miss fit for consumption of teaching materials literature in high school.Penelitian ini bertujuan untuk mendeskripsikan kepribadian tokoh yang dialami para tokoh dalam novel Rindu dan relevansinya dalam pengajaran sastra di SMA yang meliputi das es (id), das ich (ego), dan das ueber ich (superego). Ditinjau dari tiga aspek yaitu aspek bahasa, psikologi, dan latar belakang budaya. Metode penelitian ini adalah deskriptif kualitatif. Sumber data penelitian novel Rindu karya Tere Liye. Teknik analisis data penelitian adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil analisis menunjukkan data konflik kepribadian berkategori id 4, ego 72, dan supereg 25 jadi keseluruhan data konflik kepribadian 101 data. Maka disimpulkan kepribadian yang banyak muncul terdapat pada jenis kepribadian ego sebanyak 72. Selanjutnya, hasil analisis terhadap novel Rindu layak untuk dijadikan bahan ajar sastra di SMA.Kata kunci: kepribadian, novel, relevansi.